The ethics of tax evasion: relevant demographic variables within the scope of higher education students and professors - Ribeiro, César (2020)
The purpose of our study is to determine the depth of various arguments that have emerged to justify tax evasion as an ethical procedure considering several demographic variables. Data collection was done using a questionnaire addressed to professors and students of higher management and non-management courses. This instrument was based on the 18 statements reflecting the three views of tax evasion ethics used by McGee and Benk [1]. Using a 5-point Likert scale, it is intended to evaluate whether the arguments contained in the statements have an effect on the perception of tax evasion as an ethical procedure and whether the previous effect varies according to age, sex, bachelor degree and income level. A universe of 406,980 individuals was determined using official information (sample: 384 individuals). Principal Component Analysis was used, as well as the Kaiser-Meyer-Olkin Statistics in order to measure the adequacy of the input matrix. After the extraction of the components three variables were identified: “Always Ethical”, “Waste, Corruption and Injustice” and “Discrimination and Oppressive Regimes” (Cronbach's Alpha results: 0.887, 0.85 and 0.862). “Discrimination and Oppressive Regimes” is the one that has values closest to “totally agree” that tax evasion is ethical. In general, older men with higher incomes tend to disagree about the ethics of tax evasion. The originality of the study is reflected in the controversial relationship between Ethics and Evasion and the source of the data collected. Interacting with professors and students allows the business and academic components to be combined.